Implementing intersection bounds in Stata - Victor Chernozhukov; Wooyoung Kim; Sokbae Lee; Adam Rosen (Centre for Microdata Methods and Practice (cemmap), 2013)
We present the clrbound, clr2bound, clr3bound, and clrtest com- mands for estimation and inference on intersection bounds as developed by Chernozhukov et al. (2013). The commands clrbound, clr2bound, and clr3bound provide bound estimates that can be used directly for estimation or to construct asymptotically valid confidence sets. The command clrbound provides bound estimates for one-sided lower or upper intersection bounds on a parameter, while clr2bound and clr3bound provide two-sided bound estimates based on both lower and upper intersection bounds. clr2bound uses Bonferroni's inequality to construct two-sided bounds, whereas clr3bound inverts a hypothesis test. The former can be used to perform asymptotically valid inference on the identified set or the parameter, while the latter can be used to provide asymptotically valid and generally tighter confidence intervals for the parameter. clrtest performs an intersection bound test of the hypothesis that a collection of lower intersection bounds is no greater than zero. Inversion of this test can be used to construct confidence sets based on conditional moment inequalities as described in Chernozhukov et al. (2013). The commands include parametric, series, and local linear estimation procedures, and can be installed from within Stata by typing install clrbound.
Keywords: 330; clr2bound; clrbound; clrtest; clr3bound; bound analysis; conditional moments; partial identification; infinite dimensional constraints; adaptive moment selection